Social Service of Pain Management for Patients Unresponsive to Conservative Treatment - Ristiawan Muji Laksono; Taufiq Agus Siswagama; Buyung Hartiyo Laksono; Aswoco Andyk Asmoro; Priscilla Tulong; Emilia Tiara Shantikaratri; Haffidz Wahyu Aji; Yudhistira Yuliandra; Dadik Prasetya Hutama; Candra Aditiarso (Faculty of Medicine, Brawijaya University, 2022)
Pain is one of the most common complain encountered in outpatient clinic. Inadequate pain management has been widely reported. As an anesthesiologist and pain physician, we perform a social service of pain management for patients unresponsive to conservative treatment. The social service was held from April - June 2022. We enrolled thirty-two patients from other physician reference and Primary Health Care in several districts around Malang city to come to Brawijaya University Hospital with the age range of 30-80 years old. The pain interventions given to the participants mainly include prolotherapy, pulsed radiofrequency (PRF), and others. The pain measurement of the patients were assessed with Numerical Rating Scale (NRS), pre and post-intervention. The social service is performed on 32 patients (male 34,37%, female 65.62%), majority aged 60 years od and older (34.37%) with low back pain become the major complaint (43.75%). The majority of patients receive prolotherapy (68%). The mean NRS decrease from 6.19 ± 0.18 (before treatment) to 2.69 ± 0.10 (after treatment). After this social service, most patients (96.875%) have obtained better pain control after given pain interventions.